Alíquota: aspectos constitucionais e limitações à sua instituição - Seoane, Diego Sales (2011)
This work the tax rate: the constitutional aspects and limitations of its imposition - aims to study the tax rate, more specifically its constitutional regulation, and therefore the limits established to the ordinary legislator in imposing a tax rate. This theme involved the analysis of all 39 references made in the constitutional text regarding the tax rate as well as the study of other constitutional provisions that despite not using the term tax rate in its essay, refers directly to it (as is the case, for example, of constitutional provisions dealing with the Contributory Capacity and Selectivity). Still, we try to demonstrate the limits imposed upon the ordinary legislator in the imposition of the tax rates, particularly the levy of different tax rates for taxpayers subject to the same tax. The issue was raised during the analysis of scientific literature regarding the elements composing the main rule of taxation. Besides the large number of works involving the study of both the taxpayers and the tax materiality or even the tax calculation base, there are a limited number of scientific works that devote more careful attention to the tax rate, despite of many judicial discussions revolve around the tax rate. Thus, through a literature search, we almalgamate the scientific thinking about the subject of this work and, from these ideas, have formulate our own opinions in order to demonstrate the existence of limits imposed to the ordinary legislator when establishing the tax rate. The various nuances in the constitutional regulation of taxes made the search extremely difficult yet pleasant, and the result was this thesis that, far from exhausting the subject, is an invitation to discuss deeperly this important element of Tax Law: the tax rate